Antibiogram Patterns of Staphylococci isolated from the Nasal and Axilla of Healthy Individuals in Nilai - Lalita Ambigai, Sivasamugham*; Lee, Yuet Huan; Geetha, Subramaniam* (INTI International University, 2020)
An antibiogram study suggests the prescription patterns of antibiotics in a location through which, the prescription of certain antibiotics can be controlled to minimize the rise of antibiotic resistant bacteria. S. aureus, S. epidermidis and P. acnes are common bacteria of the skin, nasal and axillae. However, many of these bacteria are gaining resistance towards antibiotics. Thus, the objective of this study was to discover the antibiogram of the common microflora isolated from the axillae and nasal cavity of 25 healthy individuals aged 18-50 in Nilai. The bacterial samples were aseptically obtained, cultured in nutrient broth and streaked onto nutrient agar to obtain pure cultures. The pure cultures were subjected to Gram-staining, catalase test, and grown on mannitol salt agar. The antibiotic susceptibility testing were performed to characterize the susceptibility of the bacterial isolates towards amoxicillin, cefazolin, erythromycin, cefoxitin, trimetoprima/ sulfametoxazol, tetracycline and gentamycin on Mueller Hinton agar. Pure cultures of 78 axillae and nasal samples were screened in this study. 65.38% of the bacterial isolates were gram positive bacteria comprising of S. aureus, S. epidermidis and possibly Propionibacterium and Corynebacterium. Out of the 24 isolates of S. aureus and S. epidermidis, 18.42% were found to be sensitive to the tested antibiotics whereas, 7.89 % showed resistance to more than one antibiotic. 28% of the staphylococci showed resistance towards amoxicillin. Although amoxicillin-resistance among gram positive staphylococci has been reported previously, it is also crucial to note that the transfer of resistant bacteria is likely to increase with imprudent prescriptions of antibiotics and improper hygiene practices of individuals. Although the sample size used in this were rather small, the findings in this study could be used for a definitive antibiotic therapy among gram positive infections in Malaysia.